Pendidikan Tauhid Anak (Tarbiyatul Aulad) Dalam Persepektif Al-Qur’an - Dalimunthe, Ardiana; Wulandari, Risa; Handayani, Tati (Yayasan Rahmat Islamiyah, 2024)
Monotheism education is very much needed in the problem of educating children. With monotheistic education, children can know goodness and have noble morals. If children understand the science of monotheism, children will be sensitive to various situations they face, whether they are good or bad. This makes it easier for children to sort and choose which ones should be imitated and which ones should not. This research aims to determine early childhood education from the perspective of the Koran. The type of research used is library research, namely research carried out by collecting data or scientific writing aimed at the object of research or collecting data of a library nature. The results of this research are Tawheed Learning Strategies in UPT SPF SMP NEGERI 2 Beringin SatuÂ Atap. In early childhood learning, learning strategies are adapted to the child's developmental age, namely: 1) Exemplary, 2) Habituation, 3) Singing, 4) Tales or stories. In Islam, it is important to instill the concept of monotheism in early childhood, because the most important thing is to introduce what monotheism is. Monotheism is the foundation for Muslims, if a person truly has monotheism then he will obtain salvation in this world and the hereafter, however, without monotheism he will definitely fall into shirk and will encounter accidents in this world and accidents in the afterlife. In the Koran, there are several aspects that parents must pay attention to when educating children, such as aspects of the development of children's social behavior, morality (akhlaq) and religious appreciation.